Waste Management Issues in Indonesia: Implications for the Nation from Socio-Political Ethical Analysis - Alice Erni Husein; Jusuf Santoso Wibisono (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Waste management in Indonesia is a complex and ongoing issue affecting environmental, public health, and economic development, as well as the overall quality of life. Objective: This paper examines the issue from a socio-political and philosophical perspective, recognizing that waste is more than a technical issue it is also an ethical issue and one of social responsibility. Methods: This research uses normative qualitative research, combining philosophical analysis with systematic policy evaluation. Results: The waste crisis is interpreted as reflecting three interrelated failures: (1) individual moral failure widespread disregard for collective environmental responsibility; (2) socioeconomic injustice the disproportionate burden of poor waste management falling on marginalized communities; and (3) governance failure characterized by weak institutional coordination, poor policy implementation, and inadequate enforcement. This study contributes a normative ethical framework that bridges political philosophy and public policy analysis in the Indonesian context. Conclusion: These efforts are essential for developing fair, sustainable, and human rights-based waste management systems in the public interest. The novelty of this study lies in its application of a normative political ethics framework drawing on Suseno (2016) to systematically evaluate waste governance as a moral and institutional accountability issue, thereby bridging philosophical analysis with public policy discourse in the Indonesian context.